The antisaccade: a review of basic research and clinical studies - Everling, Stefan; Fischer, Burkhart (Neuropsychologia, 1998)
The ability to suppress reflexive responses in favor of voluntary motor acts is crucial for everyday life. Both abilities can be tested with an oculomotor task, the antisaccade task. This task requires subjects to suppress a reflexive prosaccade to a flashed visual stimulus and instead to generate a voluntary saccade to the opposite side. This article reviews what is currently known about the neural structures and processes which are involved in the performance of this task. Current data show that a variety of brain lesions, neurological diseases and psychiatric disorders result in errors, i.e. prosaccades towards the stimulus, in this task. Brain imaging studies have shown that a widely distributed cortical and subcortical network is active during the generation of antisaccades. These findings are discussed and the potential of the antisaccade task for diagnostic purposes is evaluated.